Weeds in oil palm plantations and their antifungal activity against Ganoderma boninense - GRACE FLAVYELIZ SINONG; MUHD ARIF SHAFFIQ SAHRIR; NORNASUHA YUSOFF; MUH ADIWENA; NUSAIBAH SYD ALI; MOHAMAD HILMI IBRAHIM; AZWAN AWANG; MOHD. RASHID MOHD. RAKIB (Asian Journal of Agriculture, 2026)
Abstract. Sinong GF, Sahrir MAS, Yusoff N, Adiwena M, Ali NS, Ibrahim MH, Awang A, Rakib MRM. 2026. Weeds in oil palm plantations and their antifungal activity against Ganoderma boninense. Asian J Agric 10: g100102. https://doi.org/10.13057/asianjagric/g100102. Basal Stem Rot (BSR) caused by Ganoderma boninense remains the most destructive disease of oil palm, threatening global palm oil production. Current management strategies have proven largely ineffective in providing long-term disease control, highlighting the urgent need for sustainable approaches based on natural bioactive compounds. Plant-derived metabolites represent a promising alternative due to their natural antifungal properties, environmental safety, and potential compatibility with integrated disease management systems. Weeds, in particular, are often resilient to pathogens and may serve as unexplored reservoirs of bioactive compounds with antifungal potential. The present study aimed to identify weed species associated with healthy oil palm trees and evaluate their extracts’ in vitro antifungal properties against G. boninense. Three weed species, namely Hoya carnosa (W16), Ischaemum muticum (W18), and Polygala paniculata (W19), were found exclusively in association with healthy oil palm trees. Their crude extracts were evaluated in vitro against G. boninense using solvents of varying polarity. Among them, P. paniculata exhibited the strongest antifungal activity, with both aerial and below-ground parts showing pronounced inhibition. Below-ground part extracts consistently outperformed aerial parts, particularly when extracted with methanol, which yielded the highest inhibition and lowest EC50 values, suggesting a higher concentration of bioactive metabolites in root tissues. The observed antifungal efficacy correlated with solvent polarity, emphasizing the importance of targeted extraction in isolating effective phytochemicals. These findings indicate that P. paniculata, especially its methanolic root extract, represents a promising source of natural antifungal compounds. The study highlights the potential of weed plants as unconventional reservoirs of bioactive metabolites and provides a foundation for developing eco-friendly, broad-spectrum fungicides to combat G. boninense, thereby advancing sustainable disease management in oil palm plantations.